PERLINDUNGAN HUKUM BAGI TENAGA KEPERAWATAN DI MASA PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) PADA MASA COVID-19 TERHADAP UPAH LEMBUR YANG DIKONVERSIKAN HARI LIBUR DI RUMAH SAKIT DAERAH MADANI PEKANBARU - Febiola Utami Putri; Rika Lestari; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The density of nurses' working hours during the COVID-19 period, especiallyduring the implementation of PPKM at Madani Hospital, should be clear about theamount of overtime pay for workers in accordance with Law of the Republic of IndonesiaNumber 13 of 2003 concerning Manpower and the Decree of the Minister of Manpowerand Transmigration of the Republic of Indonesia Number KEP.102 /MEN/VI/2004concerning Overtime and Overtime Pay. This thesis research aims to: find out theImplementation of the Fulfillment of Overtime Pay Rights for Nursing Workers during thePPKM Period during the Covid-19 Period at Madani Pekanbaru Hospital and know theLegal Protection for Nursing Workers during the PPKM Period during the Covid-19Period Against Overtime Pay Converted to Holidays at the Madani Pekanbaru Hospital.The type of research used by the author is sociological legal research, because inthis research the author directly conducts research at the location or place under study inorder to provide a complete and clear picture of the problem under study. This researchwas conducted at the Pekanbaru Madani Regional Hospital.The results of the analysis in the study found that: The provision of holidays as aform of "overtime pay" was never included in the work contract agreed upon by theMadani Hospital and Nurses. Nevertheless, one of the nurses said that changing overtimepay into the form of holidays was a common thing to happen, even though there was nopolicy or agreement made beforehand. In fact, not a single nurse dared to oppose theunilateral and arbitrary policies implemented by RSD Madani against nurses. LegalProtection for Nursing Workers during the PPKM Period during the Covid-19 PeriodAgainst Overtime Pay Converted to Holidays at the Madani Pekanbaru Hospital from asocial perspective such as providing nutritious food and drinks, providing securityfacilities, providing health services, providing psychologists and fulfillment of PersonalProtective Equipment which are forms of protection provided by RSD to nurses workingduring the Covid-19 pandemic, especially during the PPKM period. However, there isone protection that is not fulfilled by RSD Madani, namely "wage protection" containedin Law Number 13 of 2003 concerning Manpower. As well as not fulfilling Article 36letter e of Law Number 38 of 2014 Concerning Nursing, which nurses must "Receivecompensation for nursing services that have been provided".Keywords: Legal Protection-Nurse-Overtime Pay